"We Need to Have a Meeting": Public Housing Demolition and Collective Agency in Atlanta, Georgia. Issue 1 (2nd January 2016) - Keene, Danya E.
Abstract : The last two decades have witnessed widespread demolition of public housing and a large-scale relocation of public housing residents. Much of the current literature has examined the impact of demolition on relocated residents, focusing primarily on individual outcomes such as employment, housing quality, and health. This article examines the potential collective consequences of relocation by using data from 40 in-depth interviews conducted with relocated public housing residents in Atlanta, Georgia, to examine experiences of civic engagement and tenant activism before and after relocation. Participants describe frequent experiences of civic engagement and tenant activism in their public housing communities prior to demolition and also discuss how these collective actions often translated into meaningful gains for their communities. Participants also describe challenges associated with reestablishing these sources of collective agency in their new, post demolition, private-market rental communities where opportunities for civic engagement and tenant activism were perceived to be limited, where stigma was a barrier to social interaction, and where they experienced significant residential instability.